Career opportunities for Classical Dancers and Musicians - Nayana V. Patel (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2024)
This research paper explores different career opportunities for classical dancers and musicians available. It provides insights about advantages of studying performing arts specific to classical dance and music with respect to knowledge, artistic skills, manage- ment skills and communication skills. Research deals with in-depth analysis of benefits of choosing performing arts as career which in turn enhance skills. Knowledge - Analysing and understanding characters emotions and motive, understanding ideas with respect to historical background, profound knowledge on language, collate and contrast concepts, critical thinking, implementing techniques. Artistic Skills - creativity, ability to focus and practise vigorously for extended periods of time, create and emote. Management Skills - program planning, precise and detailed work, collaborating with other artists, time management, prudence, making best use of avail- able resource. Communication Skills - briefing on concepts of the performance, oratory skill, communicating concepts creatively. The paper intends to unfold different possible career opportunities for classical dancers and musicians based on divergent streams such as Performance, Design and Production, Academic, Health and other fields which students can opt their career path in the journey as a performing artiste. Further it explores multiple possibilities under each steam. Performance - Performer, Choreography, Acting, Mod- elling, Anchoring, Creative Director, Instrumental musician, Vocal musician, Nattuvanār, Composer. Design and Production - Lighting Designer, Costume Designer, Makeup Artist, Property and Stage designer, Sound designer, Director. Academic Teacher/Professor in schools/colleges, Dance historian or scholar, Lyricist. Health Dance therapist, Music therapist, Yoga Instructor. Other Dance Photographer and Videographer, Performance critic, Art admin- istrator, social media influencer. Research methodology followed is combination of descriptive design as existing career options are observed and Exploratory as exploring further options available. Possible limitations in this study, Limitation of access to data - ас- cess to multiple career options available. Limitation of Time - Time available to study topic in detail due to time constraints given to re- searcher. Limitation of research Design used - specific constraints might be on population of research based on selected design that might impact conclusion. Study provides gist of available types of academic courses for performing arts specific to classical dance and music, advantages, disadvantages of traditional learning against academic learning. This paper enables students to explore various career opportunities and accessibility of those options through dif- ferent platforms. Information here can be used by academic orga- nizations to improve their curriculum and aid students in the field of performing arts.